Second Screen Phenomena and News Consumption in Pakistan - Batool, Faiza; Sadiq, Dr. Najma; Dr. Ume Laila (Journal of Peace, Development and Communication, 2021)
The second screen phenomenon is a hybrid media process referring to the complementary and simultaneous use of television and a second web-connected screen for media consumption. Audience activity for news consumption relating second screen phenomenon is still less explored area. The present study examined the impact of demographic characteristics (i.e. gender, age, education, and income) on audience activity for second screen news consumption in Pakistan. An online survey based on snowball sampling was conducted from 400 respondents. The results showed that gender only plays a role in usage during post exposure. The age was comparatively a strong predictor of audience activity. It has a positive relationship with involvement during exposure and usage during post exposure phase of second screen news consumption. Our study contributes to the existing literature by identifying the predictors for changing news consumption patterns in the new media eco-system and helps in a better understanding of contemporary media audiences.